Exploring the potential anti-thyroid activity of Acetyl-L-carnitine: Lactoperoxidase inhibition profile, iodine complexation and scavenging power against H2O2. Experimental and theoretical studies - Caro Ramirez, Janetsi Yamilet (2024)
L-Acetylcarnitine (ALC), a versatile compound, has demonstrated beneficial effects in depression, Alzheimer´s disease, cognitive impairment, and other conditions. This study focuses on its antithyroid activity. The precursor molecule, L-carnitine, inhibited the uptake of triiodothyronine (T3) and thyroxine (T4), and it is possible that ALC may reduce the iodination process of T3 and T4. Currently, antithyroid drugs are used to control the excessive production of thyroid hormones (TH) through various mechanisms: (i) forming electron donor–acceptor complexes with molecular iodine, (ii) eliminating hydrogen peroxide, and (iii) inhibiting the enzyme thyroid peroxidase. To understand the pharmacological properties of ALC, we investigated its plausible mechanisms of action. ALC demonstrated the ability to capture iodine (Kc = 8.07 ± 0.32 x 105 M−1), inhibit the enzyme lactoperoxidase (LPO) (IC50 = 17.60 ± 0.76 µM), and scavenge H2O2 (39.82 ± 0.67 mM). A comprehensive physicochemical characterization of ALC was performed using FTIR, Raman, and UV–Vis spectroscopy, along with theoretical DFT calculations. The inhibition process was assessed through fluorescence spectroscopy and vibrational analysis. Docking and molecular dynamics simulations were carried out to predict the binding mode of ALC to LPO and to gain a better understanding into the inhibition process. Furthermore, albumin binding experiments were also conducted. These findings highlight the potential of ALC as a therapeutic agent, providing valuable insights for further investigating its role in the treatment of thyroid disorders.